(untitled) (Malaysian Management Journal, 2020)
The importance of debt financing to firms as a basis for decision-making cannot be over-emphasised. This implies that the maturity structure of debts becomes important for understanding the outcomes of firms’ decisions. There is a dearth of evidence from the Nigerian context in the current body of literature on factors that determine debt maturity structure of listed firms. We observed a persistent and steady decline in the average ratio of length of maturity period among non-financial firms among listed non-financial firms in Nigeria. This study examined the extent to which non-debt tax-shield, liquidity, assets intensity, diversification, investors’ confidence, growth opportunity, firm size, profitability and dividend policy determines the debt maturity structure of non-financial firms in Nigeria. The secondary data collected from the annual reports of a sample of 92 listed non-financial firms were analysed using the Two-stage Generalised Method of Moments (GMM) regression model for the period between 2010 and 2015. The results indicate that the non-debt tax-shield, liquidity, assets intensity, diversification, growth opportunity, firm size and the dividend policy significantly determine the debt maturity structure among the listed non-financial firms in Nigeria. However, the evidence is not enough to conclude that profitability and investors’ confidence determine the debt maturity structure among the non-financial firms in Nigeria. Firm diversification and liquidity appeared to have the most profound negative effect on the debt maturity structure in line with predictions of special use of debt hypothesis and the pecking order theory. Overall, it is concluded that the firm-specific factors determine the choice of debt maturity structure among Nigerian listed non-financial firms. Although the findings of the study are robust, future studies in the areas can extend the literature by identifying and investigating institutional and macroeconomic factors that drive debt maturity structure in Nigeria.